Development of Nature Based Tourism in Sultan Syarif Hasyim Grand Forest Park, Riau Province - Aziza, Bella; Muntasib, Harini; Hermawan, Rachmad (Media Konservasi, 2025)
The Nature Conservation Area of the Forest Park in Riau Province is Tahura (Forest Park) Sultan Syarif Hasyim (SSH). SSH Forest Park is a natural tourist destination located near urban areas, offering great potential for development. However, the management of Forest Park and natural tourism in SSH Forest Park is currently considered not optimal. Indonesia's biodiversity and ecosystems play a crucial role in human life, and therefore, they must be managed sustainably. One way to conserve Indonesia's biodiversity is through the sustainable use of the area, achieved through the assessment and analysis of Objects and Natural Tourism Attractions (ONTA). This research aims to conduct an assessment and analysis of SSH Forest Park Objects and natural tourism attractions, and compile the development of natural tourism and ecotourism in SSH Forest Park.  The methods employed include a literature review, field observations, assessments of the nature reserve, and interviews. The tourist attraction in Sultan Syarif Hasyim Forest Park consists of both physical and biotic aspects, with a high assessment classification (feasible) developed. The proposed natural tourism development includes wildlife tourism (primarily primate tourism) and thematic plant collection parks, featuring typical plant collections of Riau Province, plant collections of the Dipterocarpaceae family, collections of medicinal plants, and collections of fruit-producing plants.